A.W.N. Pugin - LEWIS, DAVID FRAZER (LIVERPOOL UNIV PRESS, 2021)
A.W.N. Pugin transformed the Gothic Revival from an architectural style into a popular movement. He decorated and furnished the Houses of Parliament, transformed church design, and strongly influenced British housing. This volume provides a fresh survey of his architectural work, the first single-volume overview to be published since 1971.